PERAN PENERIMAAN DIRI DAN DUKUNGAN SOSIAL TERHADAP KONSEP DIRI REMAJA YANG TINGGAL DI PANTI ASUHAN DI BALI (Jurnal Psikologi Udayana, 2016)
Adolescence is known as an important period in the formation of self-concept. However, not all adolescents can pass through these phases in the family circle. Adolescents who live in orphanages have certain background which could affect the formation of self-concept. This study aims to determine the role of self-acceptance and social support against self-concept of adolescents living in an orphanage in Bali. This study is expected to provide benefits in the formation of self-concept of adolescents living in the orphanage through the role of self-acceptance and social support. The subjects were 98 adolescents who lived in the orphanage. The sampling technique used a two stage cluster sampling. The results of multiple regression analysis showed (R) of 0.703 (F = 46 318; p < 0.05), which means that self-acceptance and social support jointly contribute to the self concept. The coefficient of determination was 0.494, meaning that effective contribution of self-acceptance and social support in explaining the variant of self-concept as much as 49.4%, and from the value of standardized beta was found that self-acceptance is more a role of self-concept with a value of 0.506 instead of 0.278 social support. It concluded that the role of self acceptance and social support were significantly important against self-concept adolescents living in an orphanage in Bali.   Keywords: Self acceptance, Social Support, Adolescents living in an orphanage.